Pro ASP.NET Web API : HTTP Web Services in ASP.NET - Ugurlu, Tugberk; Zeitler, Alexander; Kheyrollahi, Ali (Apress Imprint: Apress, 2013)
Pro ASP.NET Web API shows you how to build flexible, extensible web services that run seamlessly on a range of operating systems and devices, from desktops to tablets to smart phones-even the ones we don't know today. ASP.NET Web API is a new framework designed to simplify web service architecture. So if you're tired of interoperability issues between inflexible web services and clients tied to specific platforms or programming languages, or if you've ever struggled with WCF, this book is for you. To start with, you'll get up to speed on Web API's modern HTTP programming model, REST and your hosting options. You'll then dive into building a real application over a series of three chapters, so you can get an immediate feel for how this technology works in practice. The second half of the book features dedicated chapters on topics like routing, controllers, validation and tracing, and the authors close with discussions on performance, hosting and an all-important look at unit testing to help you prepare your application for the real world. ASP.NET Web API makes HTTP a first-class citizen of .NET. With Pro ASP.NET Web API, you can build HTTP-based web services for your company or business, expose your data to the world across different formats and devices and gain the best possible global reach for your application.